Good correlation between bone tracer uptake in SPECT/CT and intraoperative findings of chondral lesions graded with the ICRS scoring. Issue 2 (4th December 2018) - Ammann, Nora; Schiapparelli, Filippo‐Franco; Moser, Lukas B.; Rasch, Helmut; Amsler, Felix; Hirschmann, Michael T.
ABSTRACT: The question if bone tracer uptake in SPECT/CT reflects the intraoperative cartilage status of the knee is still unanswered. In this study, thirty‐three consecutive patients (male:female = 11:22; mean age ± standard deviation 61 ± 15) with bi‐ or tri‐compartmental knee osteoarthritis who underwent SPECT/CT before total knee arthroplasty (TKA) were collected. The knee was graded in eleven different anatomical regions. In each region, the maximal relative bone tracer uptake (mrBTU) was measured twice by two observers with a six weeks interval. The intraclass correlation coefficients (ICC) showed excellent correlations and mean values were used. Intraoperatively every region was assessed with the macroscopic International Cartilage Repair Society (ICRS) scoring. A factorial analysis and a non‐parametrical Spearman's correlation were calculated among the 11 knee regions on both mrBTU and ICRS scores and significant correlations were seen between regions belonging to the same knee compartment ( p  < 0.05). A non‐parametrical Spearman's correlation was also performed to investigate the correlation between rmBTU in SPECT/CT and intraoperative ICRS cartilage grading. Significant correlations were seen on the medial compartment, on the proximal femoral trochlea and on the medial patellar facet ( p  < 0.05). A significant correlation between SPECT/CT and intraoperative findings was so demonstrated in several regions. The low accuracy of the macroscopic ICRS scoring system on grade I–II lesions could have affected the missing correlations on the lateral compartment since the selected presented mainly a varus gonarthrosis. The use of an objective measure as the rmBTU could overcome the limit of the subjectivity of MRI findings in early osteoarthritis. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:522–528, 2019. Abstract : The question if bone tracer uptake in SPECT/CT reflects the intraoperative cartilage status of the knee is still unanswered. Thirty‐three consecutive patients with knee osteoarthritis who underwent SPECT/CT before total knee arthroplasty were collected. Significant correlations between maximal relative bone tracer uptake in SPECT/CT and intraoperative ICRS cartilage grading were seen for the medial compartment, the proximal femoral trochlea and the medial patellar facet. The use of the SPECT/CT could overcome the limit of the subjectivity of MRI findings.